Globalization and cross-border labor solidarity in the Americas : the anti-sweatshop movement and the struggle for social justice - Armbruster-Sandoval, Ralph, 1968- (Routledge, 2005)
This book describes how workers, unions and NGOs from four Central American countries--Guatemala, El Salvador, Honduras and Nicaragua--fought back and struggled for social justice alongside US-based unions and NGOs.